ANALISIS SEMIOTIKA JOHN FISKE PESAN PENGGUNAAN NARKOBA PADA FILM ANIMASI 3D “FICUSIA” - Alfi, Nurul Faizah; Prasetiya, Happy Yugo (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2023)
Up until now, drug use has been the main focus of the world. In Indonesia, there has been an increase in the prevalence of drug users by 0.15 percent. Using film as a medium to convey anti-drug messages is one of the many ways this can be done. This study aims to find out whether the message about the dangers of drug abuse from the film Ficusia has been conveyed properly or not. This research is a descriptive qualitative research that uses John Fiske's semiotic analysis which has several codes to analyze the object under study. There are three signs of television expressed by John Fiske, namely the Level of Reality, the Level of Representation and the Level of Ideology. The results of the study revealed that the animated film Ficusia is successful in becoming an anti-drug campaign media because it contains several factors and the impact of drug use. Apart from that, messages about the dangers of drug use have also been conveyed in this series.